Riverine forest as a significant habitat to harbor a wide range of bird species - Rajpar, M.N.; Rajpar, A.H.; Zakaria, M. (Instituto Internacional de Ecologia, 2024)
Riverine forests are unique and highly significant ecosystems that are globally important for diverse and threatened avian species. Apart from being a cradle of life, it also serves as a gene pool that harbors a variety of flora and fauna species (repeated below). Despite the fact, this fragile ecosystem harbored avian assemblages; it is now disappearing daily as a result of human activity. Determining habitat productivity using bird species is critical for conservation and better management in the future. Multiple surveys were conducted over a 15-month period, from January to March 2019, using the distance sampling point count method. A total of 250 point count stations were fixed systematically at 300 m intervals. In total, 9929 bird individuals were recorded, representing 57 species and 34 families. Out of 57 bird species, two were vulnerable, one was data deficient, one was nearly threatened, and the remaining 53 species were of least concern. The Eurasian Collard Dove – Streptopelia decaocto (14.641 ± 2.532/ha), White-eared Bulbul – Pycnonotus leucotis (13.398 ± 4.342/ha) and Common Babbler – Turdoides caudata (10.244 ± 2.345/ha) were the three first plenteous species having higher densities. However, the densities of three species, i.e., Lesser Whitethroat – Sylvia curruca, Gray Heron – Ardea cinerea and Pallas Fish Eagle – Haliaeetus leucoryphus, were not analyzed due to the small sample size. The findings of diversity indices revealed that riverine forest has harbored the diverse avian species that are uniformly dispersed across the forest. Moreover, recording the ten foraging guilds indicated that riverine forest is rich in food resources. In addition, the floristic structure importance value index results indicated that riverine forest is diverse and rich in flora, i.e. trees, shrubs, weeds and grass, making it an attractive and productive habitat for bird species.